NCMP-07. CLINICAL NEUROLOGICAL FEATURES AND ELECTROGRAPHIC PATTERNS OF PATIENTS WITH RELAPSED OR REFRACTORY LARGE B-CELL LYMPHOMA TREATED WITH AXICABTAGENE CILOLEUCEL AT MEMORIAL SLOAN KETTERING CANCER CENTER (MSKCC). (5th November 2018) - Sequeira, Alexandra; Mao, David; Chen, Xi; Avila, Edward; Mead, Elena; S Sauter, Craig; Lia Palomba, Maria; B Dahi, Parastoo; Lee Batlevi, Connie; L Shah, Gunjan; Chan, Jason; A Giralt, Sergio; et al.
Abstract: CD19-specific chimeric antigen receptor (CAR) T cell therapy is a promising treatment for hematological malignancies however is associated with neurotoxicity. Axicabtagene ciloleucel is approved to treat adult patients with relapsed or refractory large B-cell lymphoma. Here we describe the neurological features and encephalogram (EEG) patterns of patients with refractory lymphoma treated with axicabtagene ciloleucel at Memorial Sloan Kettering Cancer Center (MSKCC). We retrospectively analyzed the neurological features and EEG patterns of the first six patients with refractory lymphoma treated at MSKCC with axicabtagine ciloleucel between February and April 2018. All six patients developed neurotoxicity, with both diffuse encephalopathy and focal neurological features.None of the patients had pre-existing neurological conditions. All patients received prophylatic levetiracetam and had a long-term video EEG performed. Two patients developed neurological findings concerning for focal status epilepticus. One patient had rhythmic right arm movements followed by weakness and the EEG showed left lateralized rhythmic delta activity (LRDA) with sharp waves and attenuation possibly reflecting a post-ictal state. The second patient had right facial and bilateral eye twitching concerning for focal motor status epilepticus. The EEG showed diffuse dysfunction - rhythmic delta activity and triphasic waves. Both patients had clinical improvement with addition of fosphenytoin. The remaining four patients had EEGs showing diffuse cerebral dysfunction. Neuroimaging in all patients was unrevealing for acute or significant structural pathology. Most patients had resolving neurologic symptoms; one patient had prolonged paraparesis. CONCLUSIONS: Axicabtagene ciloleucel can lead to transient diffuse and focal neurological findings of varying severity including focal status epilepticus. EEG is useful in characterizing cerebral dysfunction however is limited in detecting epileptic events. In patients who develop clinical status epilepticus escalation of AEDs may be warranted despite EEG not fulfilling status epilepticus criteria. Further study is needed to determine whether AED escalation can optimize patient outcomes.